Prevalence of Anemia and Morphological Variation in RBC among COPD Patients admitted at a Tertiary Health Care Center, Kathmandu, Nepal - Manandhar, Seerina Adhikari; Pramanik, Tapas; Devkota, Krishna Chandra; Panta, Prem Prasad (Nepal Medical College Journal, 2021)
Many studies have depicted that anemia is one of the most common co-morbidity among Chronic Obstructive Pulmonary Disease (COPD) patients. Therefore, its correction in those patients is an important aspect of the treatment protocol. Our study was designed to explore the prevalence of anemia and morphological alteration, if any, in RBC among COPD patients. The study was conducted from November 2020 to June 2021 among the COPD patients admitted in the Medical ward of Nepal Medical College Teaching Hospital. If hemoglobin level was <13gm/dl in males and <12gm/dl in females and/or hematocrit level was <39%, the patient was considered anemic. Anemia was morphologically classified following standardized procedure with RBC indices as a reference. Among the COPD patients (n=101), 40 (39.6%) were anemic, out of which 21(52.5%) was normocytic normochromic, 10 (25%) were microcytic hypochromic, 5 (12.5%) were normocytic hypochromic, 3 (7.5%) were microcytic normochromic and (2.5%) was macrocytic hyperchromic. Anisocytosis was commonly noted (25.7%) among the COPD patients with microcytosis (20.8%) and macrocytosis (4.9%) among them. Among the patients, 23.8% showed hypochromia while only 0.9% showed hyperchromia. Polycythemia was present in 24 (23.8%) of them. Inflammatory mediators and cytokines in COPD causes a compromised response of marrow cells to erythropoietin and shortens the survival of red blood cells.